Functional neuroanatomical double dissociation of mnemonic and executive control processes contributing to working memory performance - Postle, Bradley R. (The National Academy of Sciences, 1999)
We used event-related functional MRI to investigate the neural bases of two categories of mental processes believed to contribute to performance of an alphabetization working memory task: memory storage and memory manipulation. Our delayed-response tasks required memory for the identity and position-in-the-display of items in two- or five-letter memory sets (to identify load-sensitive regions) or memory for the identity and relative position-in-the-alphabet of items in five-letter memory sets (to identify manipulation-sensitive regions). Results revealed voxels in the left perisylvian cortex of five of five subjects showing load sensitivity (as contrasted with alphabetization-sensitive voxels in this region in only one subject) and voxels of dorsolateral prefrontal cortex in all subjects showing alphabetization sensitivity (as contrasted with load-sensitive voxels in this region in two subjects). This double dissociation was reliable at the group level. These data are consistent with the hypothesis that the nonmnemonic executive control processes that can contribute to working memory function are primarily prefrontal cortex-mediated whereas mnemonic processes necessary for working memory storage are primarily posteriorly mediated. More broadly, they support the view that working memory is a faculty that arises from the coordinated interaction of computationally and neuroanatomically dissociable processes.